The Impact of Education (Level of Knowledge) on the Prevalence of Obesity in Different Urban Environments - Yuval Arbel; Yifat Arbel; Amichai Kerner; Miryam Kerner (REGION)
We investigate the impact of high-rise buildings on the prevalence of obesity in the US during 2011-2020 stratified by educated vs. non-educated populations. We use a quadratic specification that accounts for non-monotonic variation. Findings demonstrate that concentration of above 147 skyscrapers in a state is detrimental with regards to the projected prevalence of obesity. The main public policy repercussions of our study are: 1) the promotion of education for medical literacy due to the fact that for each number of skyscrapers the prevalence of obesity is lower among educated populations. 2) widening pavements, pathways and open spaces following urban development.